Enhancing Student Participation and Learning Outcomes Through Quantum Learning in Economics Classrooms - Safik Nur Taufiq; Moh. Usman Kurniawan; Denok Mugi Hidayanti (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2026)
This study explores the implementation of the Quantum Learning model in Economics education at MA As-Surur Silo Jember. It examines how teachers and students perceived its influence on classroom engagement and learning experiences. While previous studies have largely emphasized the effectiveness of Quantum Learning through quantitative measurements, limited research has explored its implementation within the contextual setting of Islamic secondary education. This study addresses this gap by proposing a contextual understanding of how Quantum Learning fosters meaningful and student-centered learning experiences in Economics classrooms. A qualitative descriptive approach was employed, involving 18 informants: one Economics teacher, two school administrators, and fifteen students. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data were analyzed through data reduction, data organization, interpretation, and conclusion drawing to identify patterns related to instructional practices and learning experiences. The findings indicate that the implementation of Quantum Learning was associated with a more interactive, participatory, and contextual learning environment. Participants described greater student engagement, confidence, and motivation during classroom activities. Teachers and students also perceived that the learning process supported students in relating economic concepts to real-life situations and fostered more meaningful learning experiences. These findings suggest that Quantum Learning provides a relevant pedagogical approach for promoting student-centered learning in Economics classrooms within the madrasah context.